2021
DOI: 10.1111/bre.12532
|View full text |Cite
|
Sign up to set email alerts
|

The formation and implications of giant blocks and fluid escape structures in submarine lateral spreads

Abstract: Lateral spread (or 'spreading') and submarine creep are processes that occur near the headwalls of both terrestrial landslides and submarine mass-transport complexes (MTCs).Both submarine creep and spread deposits may contain giant (km-scale) coherent blocks, but their transport processes remain poorly constrained. Here we use 2D and 3D seismic reflection data to determine the geometry, scale, and origin of an ancient (Late Miocene) mass-transport complex (MTC) located in the Kangaroo Syncline, offshore NW Aus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 95 publications
0
7
0
Order By: Relevance
“…The scale contrast is interpreted to be due to buried MTCs, which are typically more consolidated than undeformed background slope deposits (i.e. Shipp et al ., 2004; Sawyer, 2007; Wu et al ., 2021). Thus, the incision depth and scale of Canyon‐6 is smaller than other canyons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scale contrast is interpreted to be due to buried MTCs, which are typically more consolidated than undeformed background slope deposits (i.e. Shipp et al ., 2004; Sawyer, 2007; Wu et al ., 2021). Thus, the incision depth and scale of Canyon‐6 is smaller than other canyons.…”
Section: Discussionmentioning
confidence: 99%
“…Canyons are often associated with sand‐rich gravity flows which develop into submarine fans, which can act as high quality deepwater hydrocarbon reservoirs (Stow & Mayall, 2000; Weimer & Slatt, 2004; Steventon et al ., 2021). Mass‐transport complexes (MTCs) are gravity‐driven shear failure deposits resulting from creep, spread, slide, slump and debris‐flow processes (Posamentier & Martinsen, 2011; Wu et al ., 2021). MTCs can be extremely erosive, thus containing large volumes of sediments, with single deposits covering areas of >100 km 2 and volumes of >10 000 km 3 (Frey Martinez et al ., 2005; Moscardelli & Wood, 2016; Nugraha et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These slabs can then be softened, fractured and fragmented by high dip-angle fractures, ending up as a series of laterally spread blocks on a gentle submarine slope (Micallef et al, 2007;Baeten et al, 2014;Wu et al, 2021). Due to internal softening, deformation and sediment liquefaction, the size of these blocks often decreases with their transporting distance, before they are completely fragmented and liquefied into debrites and turbidity currents (Bull et al, 2009a;Alves, 2015;Cox et al, 2020).…”
Section: Development Of Mtcs Comprising Slide Blocksmentioning
confidence: 99%
“…In addition to the physical and internal control on pipe formation, more recent investigations have demonstrated the importance of geobodies and geomorphological structures, such as salt diapirs, masstransport complexes (MTCs), and contourites, in the initiation, modulation, and growth of fluid pipes (Oppo et al, 2021;Browne et al, 2020;Kirkham et al, 2019;Ruge et al, 2021;Wu et al, 2021). Contrary to the traditional notion that fluid pipes form from the structural crests of large anticlines (Cartwright et al, 2021a) or lateral pressure transfer zones (Stump and Flemings 2000;Flemings et al 2003), recent studies have revealed the presence of fluid pipes in several other settings.…”
Section: Introductionmentioning
confidence: 99%